Kompetensi Manajerial Kepala Sekolah Dalam Mengembangkan Kinerja Guru - Dekamoy,; Al Idrus, S. Ali Jadid; Efendi, Harja (Al-Riwayah : Jurnal Kependidikan, 2024)
This study aims to explore and analyze the contribution of principals' managerial competencies in the development of teacher performance, focusing on five core competencies: personality, managerial, entrepreneurship, supervision, and social, as stipulated by Ministerial Regulation No. 13 of 2007. Using a descriptive method with a qualitative approach, the research was conducted at SMKS Yusuf Abdussatar, Kediri District, West Lombok, by collecting primary data through in-depth interviews, observations, and documentation. The results show that the principal plays a crucial role in planning, organizational development, leadership of teachers and staff, management of facilities and infrastructure, and creating a conducive work culture, all of which significantly contribute to the improvement of teacher performance. This study provides a deep understanding of the importance of managerial competencies in achieving educational goals and offers practical strategies for principals and policymakers to enhance the quality of education through the development of managerial competencies.